A preliminary study on ultrasonic treatment effect on transverse wood permeability - Tanaka, Takashi; Avramidis, Stavros; Shida, Satoshi (Maderas. Ciencia y Tecnología, 2025)
Ultrasonic pre-treatment of small and pressure saturated Douglas-ﬁr heartwood specimens at 20 kHz ﬁxed frequency with an acoustic horn resulted in increased speciﬁc permeability coefﬁcient in both radial and tangential directions. Statistical analysis revealed that there was a high correlation between ultrasonic treatment time and speciﬁc permeability coefﬁcient. Improvement rate of permeability in both radial and tangential directions was nearly the same regardless of treatment time.